2021
DOI: 10.1109/access.2021.3130654
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal Characterization and Optimization of Monolithic 3D Complementary FET (CFET)

Abstract: For the first time, the electrothermal characteristics of a three-dimensional (3D) monolithic complementary FET (CFET) in DC operation as well as in AC CMOS operation were investigated with TCAD simulations. The self-heating effect (SHE) in a monolithic CFET is expected to be a critical problem given its highly compact architecture. DC analysis of the individual NFET and PFET devices revealed that increasing the channel width from 5.0 to 7.0 nm improved the thermal resistance up to 8.5% and the RC delay up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Owing to the high device density, CFET-based ICs are concerned about the so-called selfheating effects of performance and reliability degradations due to heat generation. 6,7) Since the thermal conductivity of Ge is lower than that of Si, 8) it is predicted that Ge devices are less likely to release the generated heat and suffer from stronger self-heating effects. In fact, several experimental studies have confirmed this prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high device density, CFET-based ICs are concerned about the so-called selfheating effects of performance and reliability degradations due to heat generation. 6,7) Since the thermal conductivity of Ge is lower than that of Si, 8) it is predicted that Ge devices are less likely to release the generated heat and suffer from stronger self-heating effects. In fact, several experimental studies have confirmed this prediction.…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the on current, the researchers designed the FETs with different channel shapes [19] - [21]. The tree-shaped channel geometry has gained much attention in the semiconductor industry, especially among these channel shapes [22]- [24]. As shown in Fig.…”
mentioning
confidence: 99%
“…The channel is constructed by linking the two nanosheets by an inter-bridge (IB), which is in the shape of a fin to form the Tree-shaped NS-FET. Without additional space, this inter-bridge provides an extra drive current for the vertically stacked MOSFETs [22]. However, in sub-10 nm devices, the space between the source and channel or the drain and channel is less and suffers from charge-sharing phenomena.…”
mentioning
confidence: 99%